Output Insecurity and Ownership Disputes as Barriers to Technology Diffusion - Oscar Camacho; Michelle R. Garfinkel; Constantinos Syropoulos; Yoto V. Yotov (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper examines both the desirability and feasibility of technology transfers in a setting where institutions governing the security of output or income are imperfect. Based on a guns-versus-butter model involving two countries (a technology leader and a technology laggard), our analysis characterizes how global efficiency and the countries' preferences over transfers depend on the nature of technology, as well as on the initial technological distance between them and the degree of output security. In the case of a general-purpose technology the leader might refuse a transfer, whereas in the case of a sector-specific technology the laggard might have such an incentive. Notably, for both types of technology, our analysis reveals the possible emergence of a "low-technology trap," wherein a technology transfer to the laggard is more likely to be blocked precisely when the laggard's initial technology is sufficiently inferior to its rival. We explore how the degree of output security and the laggard's capacity to absorb state-of-the-art technology affect the range of technological distances that generate such traps for each type of technology.
Keywords: D30; D74; F51; O33; 330; output insecurity; arming policies; power; technology transfers; sanctions